Analisis Karya Kecerdasan Buatan Italian Brainrot Dalam Perspektif Undang-Undang Hak Cipta - Aulia Khansa Nabila; Yudho Taruno Muryanto (CV. ITTC INDONESIA, 2026)
This research aims to analyze one of the works produced by artificial intelligence, specifically Italian Brainrot, in the field of image-based creations. The use of artificial intelligence technology brings its own challenges in the field of copyright law, as it gives rise to a fundamental legal uncertainty regarding whether works generated by artificial intelligence can be categorized as